Characteristics and impacts of itch in children with inflammatory skin disorders. (1st May 2021) - Fang, M.M.; Nowinski, C.J.; Lai, J.; Shaunfield, S.; Silverberg, J.I.; Rangel, S.M.; Cella, D.; Paller, A.S.
Summary: Background: Itch is a cardinal feature of paediatric disorders and can impair quality of life. However, few studies have addressed symptoms and impacts of itch in paediatric patients. Objectives: We focused on understanding the child's experience of itch and the impact of itch specifically on affected children, including comparison with the adult experience. Methods: Semistructured interviews (nine parents, 15 children with itch) explored concerns related to paediatric itch experiences and effects. Themes were compared with those of previous adult interviews. Literature was reviewed to identify the need for a more comprehensive measure of paediatric itch. Results: Itch quality, intensity, duration and environmental triggers (sweating, climate change, stress and certain fabrics) are important aspects of the child's itch experience. Skin disruption, physical function, concentration, emotional reactions, stigma and relationships/social effects are itch impact themes that emerged. No paediatric‐specific scale comprehensively captures the paediatric patient itch experience. However, differences between child and adult reports of itch‐related pain, functional limitations, fatigue and restlessness, emotional reactions to itch, and treatment effects emphasize the need for a paediatric‐specific measurement tool. Conclusions: Children and parents endorse the importance of capturing the paediatric‐focused characteristics and impacts of itch in measuring disease severity and response to intervention.